2013
DOI: 10.1089/jmf.2012.2636
|View full text |Cite
|
Sign up to set email alerts
|

Aralia cordata Inhibits Triacylglycerol Biosynthesis in HepG2 Cells

Abstract: Glycerol-3-phosphate acyltransferase (GPAT) catalyzes the first committed step in triacylglycerol (TAG) and phospholipid biosynthesis, and has been considered as one of the drug targets for treating hepatic steatosis, insulin resistance, and other metabolic disorders. The aim of this study was to investigate the GPAT inhibitors from natural products and to evaluate their effects. The methanol extract of Aralia cordata roots showed a strong inhibitory effect on the human GPAT1 activity. A further bioactivity-gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Some scholars found that the chemical composition of this plant is rich in saponins [21]. Relevant studies have also confirmed that the saponins from the plants in the same genus have antiinflammatory [22,23], anticancer [24][25][26], antiatherosclerosis [27][28][29][30], and antidiabetes [31,32] effects. However, so far, no study has reported on the effect of AAS (root bark) on intimal hyperplasia after a vascular injury.…”
Section: Introductionmentioning
confidence: 88%
“…Some scholars found that the chemical composition of this plant is rich in saponins [21]. Relevant studies have also confirmed that the saponins from the plants in the same genus have antiinflammatory [22,23], anticancer [24][25][26], antiatherosclerosis [27][28][29][30], and antidiabetes [31,32] effects. However, so far, no study has reported on the effect of AAS (root bark) on intimal hyperplasia after a vascular injury.…”
Section: Introductionmentioning
confidence: 88%
“…GPAT has been recognised as one of the drug targets for the treatment of metabolic syndrome (Ref. 57). With the improvement of living standards, the incidence of metabolic syndrome continues to increase.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…-растение, внесенное в Красную книгу России [2]. Вторичные метаболиты, входящие в состав сырья аралии, оказывают антибактериальное [3], гиполипидемическое [4], обезболивающее [5], противовоспалительное [6], адаптогенное [7] и др. [8] действие.…”
Section: Introductionunclassified